Mediated Meditation: Cultivating Mindfulness with Sonic Cradle - Vidyarthi, Jay; Riecke, Bernhard E. (ACM, 2013)
Sonic Cradle enables users to shape sound with their breath while suspended in a completely dark chamber. We conducted a qualitative investigation to understand 39 naïve participants’ subjective responses to this design artifact. Systematic analysis with 3 independent data coders produced 11 findings which richly describe the Sonic Cradle experience as clearly comparable to mindfulness meditation (e.g. clarity of mind, loss of intention). This paper shows how persuasive media have the potential to promote long-term psychological health by experientially introducing a stress-relieving, contemplative practice to non-practitioners.
Keywords: Riecke; Riecke_2013; biofeedback; conferencePapers; design; immersion; jay-vidyarthi; mindfulness; music; persuasion; psychology; research through design; self-regulation; sonic-cradle; sound; stress